Sharia Views on Music and Songs: Perspective Study of Muhammadiyah and Madzhab Four - Muthoifin; Aisha Bahaaeldin Eprahim Ali; Thufail Al-Mutawakkil; Nazar Fadli; Ahmadi Abdul Adzim (Walidem Institute and Publishing (WIP), 2023)
The purpose of this study was to uncover the law of singing and music according to the decision of the majlis tarjih and tajdid muhammadiyah and the opinions of the scholars of the four Madzhab. This research method is a type of literature, and qualitative model, which relies on the method of content analysis and comparison. The result of the study was that the difference of opinion between the tarjih council and the four Madzhab only occurred on two issues: first, the law of musical instruments, and second, singing that was hummed by certain rules that made the heart fall apart. The council of tarjih and tajdid holds that both are permissible as long as they do not contain things that are forbidden by Shari'a, and stick to the original rule of law, that is, everything is permissible. While the four Madzhab think that such singing is without the legal instrument makruh and reprehensible, either makruh which means better abandoned, as the opinion of jumhur or makruh meaning haram as hanafiyyah opinion, as if accompanied by musical instruments then they agreed on the prohibition, arguing with the evidence of the Quran, sunnah, and ijma'.